Emoticonsciousness - VOGEL, CARL (Springer, 2009)
A temporal analysis of emoticon use in Swedish, Italian, German and English asynchronous electronic communication is reported. Emoticons are classified as positive, negative or neutral. Postings to newsgroups over a 66 week period are considered. The aggregate analysis of emoticon use in newsgroups for science and politics tends on the whole to be consistent over the entire time period. Where possible, events that coincide with divergences from trends in language-subject pairs are noted. Political discourse in Italian over the period shows marked use of negative emoticons, and in German and Swedish, positive emoticons.
Multimodal Signals: Cognitive and Algorithmic Issues
PUBLISHED
COST Action 2102 and euCognition International School Vietri sul Mare, Italy, April 21-26, 2008 Revised Selected and Invited Papers
Lecture Notes in Computer Science: Volume 5398/2009
Keywords: emoticons; intercultural analysis; extra-linguistic cues; Digital Humanities; Intelligent Content & Communications; Smart & Sustainable Planet; Telecommunications; Computational linguistics